2012
DOI: 10.1371/journal.pone.0048481
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alendronate Sodium (Fosamax) to Ameliorate Osteoporosis in Renal Transplant Patients: A Case-Control Study

Abstract: BackgroundRenal transplant patients often have severe bone and mineral deficiencies. While the clinical effects of immunosuppressive agents like calcineurin inhibitors (CIs) and sirolimus on bone turnover are unclear, bisphosphonates are effective in bone recovery in these patients. Gender is significantly associated with osteoporosis and affects bone turnover, which is different in women and men. The effective gender-related site of action of bisphosphonates is unknown.MethodsInitially, we enrolled 84 kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…At baseline, patients with osteoporosis received a greater cumulative steroid dose than patients with osteopenia (1326.5 mg vs 724.5 mg; P < .01). 37 In a univariate analysis, prednisolone use was associated with osteoporosis (odds ratio [OR] = 5.18; 95% CI = 1.6-16.4, P < .01). 37 Jeffery et al 32 described prednisone as an independent predictor of low BMD (multivariate, P < .01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, patients with osteoporosis received a greater cumulative steroid dose than patients with osteopenia (1326.5 mg vs 724.5 mg; P < .01). 37 In a univariate analysis, prednisolone use was associated with osteoporosis (odds ratio [OR] = 5.18; 95% CI = 1.6-16.4, P < .01). 37 Jeffery et al 32 described prednisone as an independent predictor of low BMD (multivariate, P < .01).…”
Section: Resultsmentioning
confidence: 99%
“…37 In a univariate analysis, prednisolone use was associated with osteoporosis (odds ratio [OR] = 5.18; 95% CI = 1.6-16.4, P < .01). 37 Jeffery et al 32 described prednisone as an independent predictor of low BMD (multivariate, P < .01). Alternatively, Naylor et al 35 found greater glucocorticoid exposure was not associated with a significant change in BMD at the lumbar spine, total hip, and femoral neck ( P > .05), regardless of whether the patient had received osteoporosis treatment before.…”
Section: Resultsmentioning
confidence: 99%
“…In a case-control study, short-term weekly use of alendronate (Fosamax), an oral bisphosphonate, could significantly improve both lumbar spine BMD and bone condition, regardless of effect of immunosuppressant after a long period after renal transplantation [ 110 ]. In a long-term of low-dose weekly use of alendronate (35 mg/week) for long-term renal transplant recipients, authors found alendronate could suppress bone turnover but not fracture in kidney transplant recipients with hyperparathyroidism and chronic kidney disease [ 111 ].…”
Section: Management Of Bone Disease Before and After Organ Transplmentioning
confidence: 99%
“…The Institutional Review Board of Chang Gung Memorial Hospital has specifically waived the requirement for consent. All primary data were collected according to Strengthening the Reporting of Observational Studies in Epidemiology guidelines [15]. The form described above was referenced from the previous study [14] and Liu et al’s publication [16].…”
Section: Methodsmentioning
confidence: 99%